Effectiveness of modified gracilis muscle transplantation for anal incontinence - Li Xueqing; Zhang Zuoxing (结直肠肛门外科)
[Objectives] To explore the effectiveness of modified gracilis muscle transplantation for anal incontinence. [Methods] A total of 117 patients with anal incontinence were treated at Tianjin Union Medical Center (Tianjin Binjiang Hospital) between September 1964 and August 2021 with traditional gracilis muscle transplantation for external sphincteroplasty (gracilis muscle bundle presented with“α”encircling the anal) or modified gracilis muscle transplantation (gracilis muscle bundle presented with“U” encircling the anal). This retrospective analysis comprised 34 patients with complete follow-up data for 6 months after surgery, including 12 patients in the traditional group (receiving traditional procedure) and 22 patients in the modified group (receiving modified procedure). The followings were recorded and compared between the two groups: clinical effectiveness, anal incontinence evaluated by the Wexner anal incontinence sore before and after surgery, postoperative difficulty in defecation at squatting position (anal twist), incision infection, number of incisions, time to the first postoperative bowel movement, score of postoperative stool characteristics (the Bristol Stool Scale). [Results] The overall clinical effectiveness was not statistically different between the two groups (P>0.05). Wexner anal incontinence scores before and after surgery were comparable between the two groups (P>0.05). The two groups did not differ significantly regarding the change in Wexner anal incontinence score before and after surgery (P>0.05). Within each group, Wexner anal incontinence score decreased significantly after surgery (P<0.05), the postoperative difficulty in defecation at squatting position (anal twist) and incision infection were less in the modified group than in the traditional group (P<0.05). The modified group had significantly fewer incisions (P<0.05). The two groups did not differ significantly regarding time to the first postoperative bowel movement and score of postoperative stool characteristics (P>0.05). [Conclusion] Modified gracilis muscle transplantation is effective for anal incontinence and can improve symptoms of anal incontinence, and it is a safe procedure. Compared with traditional gracilis muscle transplantation for external sphincteroplasty, the modified procedure with simplified gracilis muscle bundle encircling and can reduce the postoperative difficulty in defecation at squatting position (anal twist) and incision infection.